PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN KARANGTANJUNG PANDEGLANG - Via Febrianti; Ratu Erlina Gentari; Syamsudin Syamsudin (Sains Manajemen, 2017)
This study aims to determine the effect of leadership and work environment to employee performance at the district office karangtanjung Pandeglang, independent variables in this study are leadership and work environment and the dependent variable is the performance of employees.